Correlation of the terms “social order” and “public order”, “social security” and “public safety” - K. O. Chyshko (Bulletin of Kharkiv National University of Internal Affairs)
It has been stated that the science of administrative law is faced with the issue of not replacing and/or unifying the terms “social order”, “public order”, “social security”, “public safety”, but rather with their coordination with each other, and as a result, it is proposed to focus on the difference between the adjectives “public” and “social”, which lies in the conditional scope of the concept “social”.